2020
DOI: 10.1111/jsap.13251
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint injections in dogs with temporomandibular joint pain: 11 cases (2015‐2019)

Abstract: To describe and evaluate the clinical application of temporomandibular joint injections using betamethasone and ropivacaine in German Shepherd dogs suffering from non-odontogenic orofacial pain due to temporomandibular dysplasia and/or osteoarthritis. Materials and MethOds: Outcomes in dogs presented with clinical signs of non-odontogenic orofacial pain associated to temporomandibular joint dysplasia and/or arthritis and treated with a temporomandibular joint injection were retrospectively-prospectively evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…None of the 32 dogs with TMJ osteoarthritis had subchondral cysts in the mandibular head, therefore suggesting that subchondral cysts are not a feature of TMJ osteoarthritis. Subchondral cysts were not described when CT 15,24 and radiography [11][12][13][14][16][17][18] were used to evaluate dogs suffering from TMJ dysplasia, although it is unlikely that such small lesions would have been visible on radiographs due to the superimposition with other bones of the skull in this region. Although in the present study, subclinical TMJ dysplasia and degenerative changes could not be completely excluded, grades A to B2 were deemed unlikely to be associated with symptomatic TMJ dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…None of the 32 dogs with TMJ osteoarthritis had subchondral cysts in the mandibular head, therefore suggesting that subchondral cysts are not a feature of TMJ osteoarthritis. Subchondral cysts were not described when CT 15,24 and radiography [11][12][13][14][16][17][18] were used to evaluate dogs suffering from TMJ dysplasia, although it is unlikely that such small lesions would have been visible on radiographs due to the superimposition with other bones of the skull in this region. Although in the present study, subclinical TMJ dysplasia and degenerative changes could not be completely excluded, grades A to B2 were deemed unlikely to be associated with symptomatic TMJ dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…2 TMJ pseudoankylosis in dogs at a young age will likely result in development of lifelong malocclusion despite surgical treatment. 10,28 Osteoarthritis is the most common TMJ disorder in dogs and generally associated with other TMJ pathology. 12,28 It is assumed that dogs with TMJ pseudoankylosis may be at an increased risk of developing TMJ osteoarthritis in either joint, and may present with pain on opening and closing the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence of pseudoankylosis may occur and require further surgical intervention; however, most dogs retained a similar vmROM at long‐term follow‐up when compared to post‐operative assessment, and dogs did not display evidence of pain, discomfort or difficulty eating 2 . TMJ pseudoankylosis in dogs at a young age will likely result in development of lifelong malocclusion despite surgical treatment 10,28 . Osteoarthritis is the most common TMJ disorder in dogs and generally associated with other TMJ pathology 12,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study 3DVR images of the TMJ were greatly descriptive, showing every detail of the TMJ. Until now, 3DVR images of TMJ have only been briefly studied when focusing on different alterations in craniomandibular osteopathy, dysplasia [6], mandible luxation [6], post-traumatic ankylosis [23], sarcoma in the caudal portion of mandible [24], mandible osteomyelitis [25], fractures secondary to septic arthritis or osteomyelitis [25] or even to fit the site of puncture of a joint [31]. These studies showed lateral and rostrolateral views of the TMJ, but only Mielke et al 2017 [29] showed ventral images of the TMJ of dogs of different breeds, relating its anatomical positions with tympanic bullae.…”
Section: Discussionmentioning
confidence: 99%